Role of alumni / Angelyca Hendry - Hendry, Angelyca (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
Volunteering and financial support from Alumni is crucial to the continued growth of any institution of higher learning. By creating avenues for stronger links between alumni, current students, and the institution, it may bring significant advantages in enhancing the educational experience of the student. Because every alumnus/a has gone through the process of being a student and graduating in their own unique manner, they all have something distinctive to offer the institution.